Diagnostic value of contrast-enhanced ultrasound for the depth of myometrial infiltration in early endometrial cancer: a meta-analysis - Li, Siqi; Liang, Yingying; Wang, Jiaxun (Frontiers in Oncology, 2025)
ObjectivesGlobally, endometrial cancer (EC) is currently one of the most common gynecologic malignancies among females. Preoperative infiltration depth analysis is important for disease progression and prognostic impact. This study aimed to evaluate the diagnostic value of contrast-enhanced ultrasound (CEUS) in the infiltration depth analysis of EC.MethodElectronic databases PubMed, Embase, Cochrane Library, Web of Science, CNKI, Wanfang, and VIP were searched for more extensive literature on CEUS in the diagnosis of myometrial infiltration in EC patients up to March 29, 2024. Cochran Q and I² were used to assess the heterogeneity of eligible studies. Sensitivity (SEN), specificity (SPE), positive likelihood ratio (PLR), negative likelihood ratio (NLR), and diagnostic odds ratio (DOR) were analyzed for each clinical outcome using a bivariate random effects model. Summary receiver operating characteristic (SROC) curves were also generated.ResultsIn total, 23 papers with 1247 EC patients were included in the meta-analysis. The SEN, SPE, PLR, NLR, and DOR for the diagnosis of deep myometrial infiltration (DMI) of EC using CEUS were 0.84 [95% confidence interval (CI): 0.79, 0.89], 0.92 (95%CI: 0.90, 0.94), 11.05 (95%CI: 8.00, 15.25), 0.17 (95%CI: 0.12, 0.23), and 64.91 (95%CI: 37.11, 113.52), respectively. The area under the curve (AUC) was 0.95 (95%CI: 0.93, 0.97). For the diagnosis of superficial myometrial invasion (SMI) of EC by CEUS, the SEN, SPEN, PLR, NLR, DOR and AUC were 0.91 (95%CI: 0.85, 0.95), 0.80 (95%CI: 0.64, 0.90), 4.55 (95%CI: 2.34, 8.85), 0.11 (95%CI: 0.06, 0.21), 41.40 (95%CI: 12.14, 141.13), and 0.94 (95%CI: 0.91, 0.95), respectively.ConclusionCEUS might be a reliable and practical technique for EC myometrial infiltration diagnosis. More clinical data and studies are still needed to confirm these results in the future.